Application of maximum entropy principle for estimation of droplet-size distribution using internal flow analysis of a swirl injector. (September 2016) - Hosseinalipour, Seyed Mostafa; Karimaei, Hadiseh; Movahednejad, Ehsan; Ommi, Fathollah
The maximum entropy principle is one of the first methods, which have been used to predict droplet size and velocity distributions of liquid sprays. Due to some drawbacks in this model, the predicted results do not match well with the experimental data. This paper presents a different approach for improving the maximum entropy principle model. It is suggested to improve the available energy source in the maximum entropy principle model equation by numerical solution of flow inside the injector based on the computational fluid dynamics technique. This will enhance the calculation accuracy of the turbulent kinetic energy of the output spray. Application of this procedure enhances the model predictions. The liquid sheet properties resulted from the analysis are also applied for calculation of the momentum source in the maximum entropy principle model. The proposed model is applied to predict the droplet size distribution of a hollow-cone spray formed by a swirl injector. The results show a better agreement with the available experimental data than the results of prior models.